HIP HOP AS A REFLECTION OF AMERICAN VALUES: A SEMIOTICS ANALYSIS ON SAVE THE LAST DANCE AND STEP UP MOVIES - Naris Eka Setyawati (Universitas Gadjah Mada, 2016)
This study examines seven movies that are based on characters created by Duane Adler. They are two Save the Last Dance and five Step Up movies. This discussion is a library research which is conducted within the framework of American Studies approach under the scope of history, social, and culture. This research uses Barthes’ semiotics theory on myth to analyze the depiction of American phenomena in the movies.The objectives of this study are to examine the portrayal of Hip Hop in United States of America and to analyze the reflection of American values through movies. The discussions on the topic reveal that Hip Hop becomes the source for movies’ narratives. It is manifested in hip hop related scenes of the movies. They portray signs of rebellion and juvenile delinquency in the first order-semiological system. These portrayals reflect American values of rebellion and freedom. Moreover, life struggle and American belief in the land of opportunity play the signs in Barthes’ second order-semiological system. The American values reflected through the discussions are competitiveness, hard work, determined, optimism, and materialism.Keywords: Hip Hop, hip hop, popular culture, semiotics, American values